Rating of growth of heifers of different lines of created simental meat breed - Дедова, Л. О. (Scientific Progress & Innovations, 2012)
The results of researches of growth of heifers of different lines of created simental meat breed are given. It is proved that linear heifers differ from others with live weight which testifies the capacity for high meat productivity. Taking into account the modern requirements of market economy, the major direction of a selection presents creation of a new Ukrainian simental meat bread on the base of modern simental meat breed, capable during great while to keep high intensity of growth at the slow accumulation of fat.